2018
DOI: 10.3390/ani8110215
|View full text |Cite
|
Sign up to set email alerts
|

Can Donkey Behavior and Cognition Be Used to Trace Back, Explain, or Forecast Moon Cycle and Weather Events?

Abstract: Simple SummaryDonkeys have been traditionally attributed the ability to inform humans about the environment. Carefully observing the behavior and cognitive reactions of donkeys in their habitat may enable to quantify such reactions to develop informative mathematical models. These models can be used to explain present environmental situations, trace back past events or even predict future conditions. Our results suggest, environmental stressing situations may affect donkeys in a way that they register the cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Individual personality was scored using an adaptation of the questionnaire proposed by Navas et al [ 38 ], and French [ 39 ]. The aforementioned methodology has been previously used to evaluate behavioural patterns in problem-focused coping styles, the genetic background behind them and the conditioning factors involved in donkeys [ 24 , 27 , 28 , 35 , 40 ]. A questionnaire was completed by ten observers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual personality was scored using an adaptation of the questionnaire proposed by Navas et al [ 38 ], and French [ 39 ]. The aforementioned methodology has been previously used to evaluate behavioural patterns in problem-focused coping styles, the genetic background behind them and the conditioning factors involved in donkeys [ 24 , 27 , 28 , 35 , 40 ]. A questionnaire was completed by ten observers.…”
Section: Methodsmentioning
confidence: 99%
“…The expression degree of a total of eighteen behavioural traits was ordinally rated from 1 to 10 with these values representing the minimum and maximum extremes in the scale, respectively. The description of each of the levels comprising each of the traits in the scale was accessed from Navas et al [35] and Navas González, et al [40], and a summary of the descriptors, scales, and extreme adjectives used is shown in Table 1. Since sample size was a limitation in this study, parametric assumptions were tested to decide on the most appropriate statistical approach to follow.…”
Section: Personality Evaluationmentioning
confidence: 99%
“…The standardization and development of the tests and scales was described in a previous stage of the study (Navas et al, 2017a;Navas González et al, 2018b) and is summarized in Figure 1. Statistical verification that tests being used are in fact measuring the constructs they are intended to measure and whether they can do so with internal reliability was performed in two previous studies (Navas et al, 2017a;Navas González et al, 2018a).…”
Section: Behavioral Record Registrationmentioning
confidence: 99%